WAKTU DAN VOLUME PEMBERIAN AIR PADA BIBIT KELAPA SAWIT(Elaeis Gueneensis Jacq) DI MAIN NURSERY - Sukma Rizki Dwiyana; Sampoerno '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Palm oil ( elaeis guineensis jacq ) is a important plantations that are supporting Indonesian economy. To get a good seed of coconut palm we should watch the time and volume of water supply, because this is more effective. This research aims is to get a good combination treatment of time and water volume towards palm oil seed growth on main nursery and implemented in green house of UPT field, at Agriculture Faculties, University of Riau. this experiment using completly randomized design ( CRD ) factorially. Consisting of 2 factors: factors I is the time ( W) which is: W1 = 7.30 am, W2 = 2 pm, W3 = 17 pm and factors II were the water volume (A): A1 = 1,0 liters/polybag/day, A2 = 1,5 liters/polybag/day , A3 = 2,0 liters/polybag/day , with 3 repetition and every unit consisting by 27 experiment unit. each unit consisting 2 seeds and total population is 54 seed. Parameter that observed is the addition of plant high, the addition of leaves , the addition of excrescence diameter and leaf wide. The result showed the best combination time is 7.30 am with water volume 2,0 liters/polybag/day towards the parameter of plant high and leaf ammount. The treatment of 2 pm with the water volume 1.5 liters/polybag/day significantly showed on the parameter of leaf wide. Keyword : palm oil, time of water supply, water volume